OP0020 Validation of new systemic lupus erythematosus classification criteria. (12th June 2018) - Aringer, M.; Costenbader, K.H.; Brinks, R.; Boumpas, D.; Daikh, D.; Jayne, D.; Kamen, D.; Mosca, M.; Ramsey-Goldman, R.; Smolen, J.S.; Wofsy, D.; Diamond, B.; et al.
Abstract : Background: This 4 phase project 1 jointly supported by EULAR and ACR has led to draft criteria. 2 Objectives: To simplify and validate the new criteria in a large international cohort. Methods: 23 expert centres each contributed up to 100 patients with SLE and with non-SLE diagnoses. Diagnoses were verified by 3 independent reviewers for 1, 193 SLE and 1059 non-SLE patients. 500 randomly selected SLE and non-SLE patients formed the derivation cohort and the remainder the validation cohort. Results: The criteria were fine-tuned and simplified, using ANA of ≥1:80 as entry criterion and a classification threshold of 10. Sensitivity was close to the SLICC 2012 criteria, specificity maintained at the level of the ACR 1997 criteria. This performance was independently confirmed in the validation cohort. Conclusions: The new criteria developed with EULAR/ACR support achieved sensitivity close to the SLICC criteria, while maintaining the specificity of the ACR criteria. References: [1] Aringer, et al. Ann Rheum Dis2017;76(S2):4. [2] Tedeschi, et al. Ann Rheum Dis2017;76(S2):50. Disclosure of Interest: None declared